Reverse fountain flow of phosphatidylinositol‐3, 4‐bisphosphate polarizes migrating cells. (15th February 2021) - Li, Xiaoguang; Pal, Dhiman Sankar; Biswas, Debojyoti; Iglesias, Pablo A; Devreotes, Peter N
Abstract: The ability of cells to polarize and move toward external stimuli plays a crucial role in development, as well as in normal and pathological physiology. Migrating cells maintain dynamic complementary distributions of Ras activity and of the phospholipid phosphatidylinositol‐3, 4‐bisphosphate (PI(3, 4)P2). Here, we show that lagging‐edge component PI(3, 4)P2 also localizes to retracting leading‐edge protrusions and nascent macropinosomes, even in the absence of phosphatidylinositol 3, 4, 5‐trisphosphate (PIP3). Once internalized, macropinosomes break up into smaller PI(3, 4)P2‐enriched vesicles, which fuse with the plasma membrane at the rear of the cell. Subsequently, the phosphoinositide diffuses toward the front of the cell, where it is degraded. Computational modeling confirms that this cycle gives rise to stable back‐to‐front gradient. These results uncover a surprising "reverse‐fountain flow" of PI(3, 4)P2 that regulates polarity. SYNOPSIS: In migrating cells, phosphatidylinositol‐3, 4‐bisphosphate (PI(3, 4)P2) is concentrated at the trailing edge, where it contributes to the local inhibition of Ras activity and actin polymerization. Here, a front‐to‐rear membrane "reverse fountain flow" is shown to maintain the polarity of migrating Dictyostelium cells. PI(3, 4)P2 appears de novo on nascent macropinosomes at the front of migrating cells. PI(3, 4)P2 is delivered to the rear of the cell through a series of vesicular transport steps. PI(3, 4)P2 then diffuses along the plasma membrane towards the front, where it is degraded. Dictyostelium mutants with impaired vesicle trafficking exhibit reduced PI(3, 4)P2 levels at the rear and PI(3, 4)P2 accumulation in intracellular vesicles A stochastic mathematical model confirms the role of polarized delivery in establishment of a stable PI(3, 4)P2 gradient. Abstract : Macropinosome‐dependent delivery of the phospholipid PI(3, 4)P2 to the trailing edge of the cell establishes its polarized distribution required for correct migratory behavior.